Preparation method of sandwich type immunomagnetic beads with high thermal stability

By crosslinking the surface of the sandwich polystyrene magnetic beads to form an epoxy-based polymer layer, the problem of insufficient thermal stability of the magnetic beads in high temperature environments is solved, and higher thermal stability and long-term storage stability are achieved.

CN119534832APending Publication Date: 2025-02-28ZHEJIANG UNIV OF TECH

Patent Information

Application Number
CN202411692040.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing sandwich polystyrene magnetic beads have insufficient thermal stability in high temperature environments. Long-term storage may lead to the aggregation of magnetic beads and affect their performance.

Method used

The thermal stability of the bead is enhanced by introducing a crosslinked epoxy polymer layer into the outer layer of the bead. The method includes cross-linking on the surface of polystyrene microspheres to form an epoxy polymer layer, forming a stable epoxy group, and improving the thermal stability and mechanical properties of the magnetic beads.

Benefits of technology

It significantly improves the thermal stability and long-term storage stability of the magnetic beads, and enhances its structural integrity and capture capabilities under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119534832A_ABST
    Figure CN119534832A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of sandwich type immunomagnetic beads with high thermal stability, which comprises the following steps: by taking polystyrene microspheres as a template, introducing oil-phase Fe3O4 nanoparticles into the polystyrene microspheres through a swelling method, and then carrying out hydrolytic condensation reaction on the surface of a microsphere assembly by utilizing n-octyltrimethoxysilane OTMS to obtain the sandwich type immunomagnetic beads with high thermal stability. The preparation method comprises the following steps: carrying out surface amination modification on a silicon dioxide thin layer which is grown by hydrolysis of tetraethoxysilane TEOS to realize coating of an outermost organic shell layer, carrying out surface amination modification, and carrying out cross-linking on 1, 4-butanediol diglycidyl ether and erythritol on the surface to form an epoxy polymer layer so as to obtain the sandwich-type immunomagnetic bead with a cross-linked epoxy polymer layer introduced to the outer layer. According to the epoxy group modification process on the surface of the magnetic bead, a direct cross-linking modification process is adopted, so that the operation steps are simplified, and the obtained epoxy group magnetic bead is ensured to show excellent biocompatibility. In addition, the method omits the tedious process of functional group activation, and allows direct coupling with the antibody, thereby greatly improving the efficiency and convenience of the experiment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing sandwich-type immunomagnetic beads with high thermal stability. Background Art

[0002] Sandwich polystyrene magnetic beads are a versatile nano- or micro-scale material that is mainly composed of polystyrene and forms uniformly magnetized spherical particles. These magnetic beads have a unique three-layer structure: the core is polystyrene, the surface is loaded with magnetic substances such as ferroferric oxide, and the outer layer is a polymer with functional groups that can specifically bind to biological molecules such as nucleic acids and proteins. Magnetic beads play a key role in many fields such as nucleic acid extraction, purification, fragment screening, cell separation, protein purification, and chemiluminescence detection. They are particularly popular in high-throughput sequencing experiments due to their automation and high-throughput characteristics. However, the chemical structure of the polymer has a significant impact on its thermal stability. Although the aromatic rings in polystyrene are more stable than aliphatic rings, the oxygen atoms and carbonyl groups that may be contained in sandwich polystyrene magnetic beads have relatively weak chemical bond energies and are more likely to decompose during heating. In addition, the structure of the magnetic beads may include an organic / inorganic double silica layer coating, which, while providing ideal stability and dispersibility, may affect the overall thermal stability of the magnetic beads at high temperatures. As for the stability of the protein or antibody coupled magnetic bead surface, it mainly depends on the surface properties. If the magnetic bead surface is not modified or the modification is unstable, the antibody may only be passively adsorbed to the magnetic bead surface through hydrophobic interactions. This method cannot control the final direction of the attached molecules, nor can it ensure the specificity and stability of the captured molecules. Therefore, in order to improve the performance and stability of magnetic beads, the surface modification and chemical structure of the magnetic beads need to be carefully designed and optimized.

[0003] In order to improve the thermal stability of polystyrene magnetic beads, common strategies include using cross-linking agents to enhance their network structure, or introducing other monomers such as acrylonitrile and butadiene during the synthesis process to form copolymers. In the preparation process of magnetic beads, it is a technical challenge to achieve uniform size of magnetic beads, high magnetic content and uniform distribution of surface functional groups. At the same time, the thermal stability and chemical stability of magnetic beads are also the focus of research. Researchers have developed a variety of preparation methods, including emulsion polymerization, coprecipitation, in situ polymerization, etc., and improve the performance of magnetic beads by surface modification and functionalization. There are many commercial magnetic bead products on the market, such as Dynabeads series and JSR series, which are widely used in immunoassays, molecular diagnosis and other fields. JSR's sandwich magnetic beads are based on polystyrene. By mixing polystyrene microspheres with magnetic materials (such as ferroferric oxide), the magnetic materials are evenly distributed on the surface or inside of polystyrene microspheres by physical adsorption or chemical bonding to form polystyrene microspheres. Functional groups such as carboxyl and amino groups are introduced on the surface of magnetic polystyrene microspheres by chemical modification to achieve specific binding in biological analysis. Usually, a layer of silica is modified on the outside of the magnetic beads, which not only prevents the leakage of magnetic particles, but also ensures the structural stability of the magnetic beads. However, even if the magnetic beads have high thermal stability and long-term storage stability, during long-term storage, the magnetic beads may agglomerate due to physical or chemical factors, resulting in inability to disperse, affecting the performance of the magnetic beads. Magnetic beads may be stratified when left standing for a long time, affecting their suspension stability, which is particularly important in fields such as chemiluminescent immunoassays. The surface modification layer of the magnetic beads may degrade due to long-term storage, resulting in increased nonspecific adsorption, affecting purity and stability. In addition, if there are exposed hydrophobic parts on the surface of the magnetic beads, they may produce nonspecific adsorption with the labeled detection antibodies, resulting in increased background signals. Therefore, in order to maintain the performance and stability of the magnetic beads, it is necessary to strictly control the storage conditions and adopt appropriate surface modification techniques. By modifying a soft polymer layer outside the hard template silicon layer, the synergistic effect of the two layers of materials can be achieved, which can not only ensure the stability of the magnetic particle structure, but also extend the long-term storage stability of the magnetic beads and improve the biocompatibility of the magnetic bead surface.

[0004] Researchers have adopted a variety of strategies to achieve this goal: 1) Adding polyamine cross-linkers: Introducing polyamine cross-linkers during the epoxy resin coating process not only enhances the coating effect, but also makes surface modification easier. 2) Surface activation treatment: First, the surface of the magnetic beads is activated, such as using a silane coupling agent to introduce epoxy groups or other active groups, and then fix proteins or other ligands by covalent bonding. 3) In situ polymerization of epoxy monomers: In situ polymerization of monomers containing epoxy groups on the surface of the magnetic beads to form a uniform epoxy resin coating, which enhances the stability and biocompatibility of the magnetic beads. 4) Modification with GMA monomers: The surface of ferroferric oxide magnetic beads is modified using monomers such as GMA (glycidyl methacrylate). GMA can react with the hydroxyl groups on the surface of the magnetic beads to form a stable epoxy coating.

[0005] The common goal of these methods is to improve the performance of magnetic beads and make them more reliable and effective in biomedical applications. Through these fine surface modification techniques, the stability and functionality of magnetic beads have been significantly improved, laying a solid foundation for the application of magnetic beads in various biotechnology and medical diagnostic fields.

[0006] As an important biomedical and analytical chemistry tool, immunomagnetic beads are in growing demand worldwide. The immunomagnetic beads available on the market are known for their diverse surface structures and carrier properties. Sandwich polystyrene magnetic beads, with their special structure of inner core magnetic material and outer polystyrene polymer layer, have become a star product in this field. This unique structure gives the magnetic beads excellent physical and chemical properties, enabling them to play a key role in many fields. However, the existing sandwich polystyrene magnetic beads have insufficient thermal stability in high temperature environments, and long-term storage may cause the magnetic beads to aggregate, affecting their performance.

[0007] The present invention effectively improves the thermal stability of magnetic beads by introducing a cross-linked epoxy polymer layer into the outer layer of magnetic beads. This innovative surface modification technology not only enhances the stability of magnetic beads, but also has an application range not limited to magnetic beads, but can also be extended to other materials containing amino groups on the surface, further broadening its application prospects.

[0008] The reason why epoxy polymer-coated magnetic beads can improve their thermal stability is mainly due to the protective epoxy layer formed on the outer layer of the magnetic beads. This epoxy layer acts as a barrier in high-temperature environments, protecting the inner core of the magnetic beads from direct thermal attack, thereby enhancing the overall heat resistance of the magnetic beads. In addition, the chemical bonding between the epoxy polymer and the active groups on the surface of the magnetic beads is strengthened, and this strengthened chemical bond can more effectively resist the destructive effects of high temperatures. The core-shell structure magnetic microbeads formed by this coating process have significantly improved thermal stability because this structure can effectively isolate the inner core, making it less susceptible to damage from high temperatures. At the same time, the epoxy polymer coating also enhances the mechanical properties of the magnetic beads, such as impact strength and tensile strength. The improvement of these properties helps the magnetic beads maintain their structural integrity under high temperature conditions and further enhances their thermal stability. In short, the epoxy polymer coating provides a solid protective barrier for the magnetic beads, making them more stable and reliable when facing high temperature challenges. Summary of the invention

[0009] In view of the technical problems in the prior art such as the disadvantage that polystyrene magnetic beads easily lose stability under high temperature conditions, the purpose of the present application is to provide a method for preparing sandwich-type immunomagnetic beads with high thermal stability. This method significantly enhances the thermal stability of the magnetic beads by cross-linking a layer of epoxy polymer on the surface of the magnetic beads, thereby improving their long-term storage stability.

[0010] The present application synthesizes cross-linked polystyrene microbeads with uniform particle size and good monodispersity by dispersion polymerization, introduces magnetic nanoparticles Fe3O4 into polystyrene microbeads by swelling method, and then uses n-octyltrimethoxysilane (OTMS) to silanize the surface of microspheres, and uses tetraethyl orthosilicate (TEOS) to coat the outermost organic shell layer to prevent leakage of magnetic particles. On this basis, the surface of the synthesized silicon-coated polystyrene magnetic beads is aminated with 3-aminopropyltrimethoxysiloxane (APTMS), and then 1,4-butanediol diglycidyl ether (BDE) and erythritol (Ery) are cross-linked into a polymer layer on the surface of the sandwich polystyrene magnetic beads in a certain ratio, and the surface is modified with epoxy groups. When the sandwich immunomagnetic beads of the present application are used in subsequent applications, they can be directly coupled with antibodies through the epoxy groups on the surface of the cross-linking layer without the need for functional group activation, thereby solving the problems of poor thermal stability and poor dispersibility of the magnetic beads and improving the capture ability of the magnetic beads to obtain sandwich polystyrene magnetic beads with good monodispersity and thermal stability.

[0011] The technical solution adopted by the present invention is as follows:

[0012] A method for preparing sandwich immunomagnetic beads with high thermal stability, using polystyrene microspheres as templates, introducing oil-phase Fe3O4 nanoparticles into polystyrene microspheres by a swelling method, and then using n-octyltrimethoxysilane (OTMS) to undergo a hydrolysis condensation reaction on the surface of the microsphere assembly to achieve a phase transfer of the microsphere assembly from an organic phase to an aqueous phase, and then The method uses tetraethyl orthosilicate (TEOS) to hydrolyze and grow a thin layer of silicon dioxide to achieve the coating of the outermost organic shell layer to prevent the leakage of magnetic particles. The obtained silicon-coated polystyrene magnetic beads are then surface-amino-modified, and then 1,4-butanediol diglycidyl ether (BDE) and erythritol (Ery) are cross-linked on their surface to form an epoxy polymer layer, thereby obtaining a sandwich-type immunomagnetic bead with a cross-linked epoxy polymer layer introduced into the outer layer.

[0013] Furthermore, the oil phase Fe3O4 nanoparticles are assembled on polystyrene microspheres in two layers, and the assembly steps are as follows:

[0014] S1 one-layer assembly: After the microsphere template is swollen in toluene good solvent at room temperature overnight, the first part of oil phase Fe3O4 nanoparticles is added and ultrasonicated at room temperature for 10-30min, magnetically separated, and then the microsphere assembly is shrunk with ethanol poor solvent;

[0015] S2 two-layer assembly: add an ethanol dispersion of polyethyleneimine PEI to the assembly of step S1, the mass ratio of the microsphere template to PEI in the assembly is 1:0.5-2, rotate and incubate at room temperature at a speed of 100-400 rpm for 1-3 hours, and wash with ethanol after magnetic separation to obtain the middle layer assembly filled with PEI, then add the second part of oil phase Fe3O4 nanoparticles and n-hexanol-toluene mixed solution, ultrasonicate at room temperature for 10-30 minutes, magnetic separation, and wash with ethanol to complete the preparation.

[0016] Furthermore, the mass ratio of the first part of oil-phase Fe3O4 nanoparticles to the second part of oil-phase Fe3O4 nanoparticles is 1:0.5-2, preferably 1:0.8-1.2, and the ratio of the total mass of the two parts of oil-phase Fe3O4 nanoparticles to the mass of the microsphere template is 1-2:1, preferably 1.5-1.6:1.

[0017] Furthermore, in the n-hexanol-toluene mixed solution of step S2, the volume ratio of n-hexanol to toluene is 2-4:1, preferably 3:1; the dispersion concentration of the second part of oil phase Fe3O4 nanoparticles in the n-hexanol-toluene mixed solution is 1-5 mg / mL.

[0018] Furthermore, the preparation method of the oil-phase Fe3O4 nanoparticles is as follows: add iron salt, dodecanediol, dibenzyl ether, oleic acid and oleylamine to a reaction bottle, dissolve the solid by ultrasound, fill with nitrogen to completely replace the air in the reaction bottle, raise the temperature to 180-200°C and vigorously stir for 20-40 minutes, then continue to raise the temperature to 285-300°C, vigorously stir for 1-3 hours, and then terminate the reaction; after cooling to room temperature, add methanol to the crude solution to precipitate the magnetic particles generated by the reaction, magnetically separate, absorb the supernatant, add chloroform to the precipitate to dissolve the magnetic particles, add methanol again to precipitate the particles, and finally dissolve the precipitate and store it in toluene for later use.

[0019] Furthermore, in the preparation method of the oil-phase Fe3O4 nanoparticles, the iron salt is ferric acetylacetonate, and the feed ratio of the iron salt, dodecanediol, dibenzyl ether, oleic acid and oleylamine is (0.6-0.8) g: (1.8-2.4) g: (8-12) mL: (3-5) mL: (3-5) mL.

[0020] Furthermore, the silicon-coated polystyrene magnetic beads are amino-modified in three steps, and the process is as follows:

[0021] 1) Disperse the silicon-coated polystyrene magnetic beads in ethanol, add the first part of 3-aminopropyltriethoxysilane APTMS and ammonia water, and react at 100-300 rpm in a shaker for 1-3 hours;

[0022] 2) Then, add the second part of 3-aminopropyltriethoxysilane APTMS and continue to react for 1-3 hours, then add the third part of 3-aminopropyltriethoxysilane APTMS and continue to react for 1-3 hours, separate by magnetic separation, and wash with ethanol and water in turn, and the amino modification is completed;

[0023] The volume ratio of the first part, the second part and the third part of APTMS is 1:0.8-1.2:0.8-1.2, the total volume of the three parts of APTMS and the mass ratio of the microsphere template in the silicon-coated polystyrene magnetic beads is 0.5-1:1, the volume unit is μL, and the mass unit is mg;

[0024] Step 1) The mass concentration of the aqueous ammonia is 25-28%, and the volume of the aqueous ammonia is 0.5-1% of the volume of the ethanol;

[0025] Step 1) The concentration of silica-coated polystyrene magnetic beads dispersed in ethanol is 1-10 mg / mL.

[0026] Furthermore, the preparation method of the epoxy polymer layer is as follows: the aminated magnetic beads, 1,4-butanediol diglycidyl ether BDE and erythritol Ery are dispersed in a borate buffer solution with a pH of 9.0, reacted at a speed of 100-300 rpm in a shaker at room temperature for 20-30 hours, and after the reaction is completed, magnetic separation is performed and washed with ultrapure water to complete the preparation.

[0027] Furthermore, the mass ratio of BDE to Ery is 2-3:1.

[0028] Furthermore, the mass ratio of the BDE to the microsphere template in the aminated magnetic beads is 1-16:1, preferably 4-8:1.

[0029] The key points of the present invention include:

[0030] 1. The present invention forms a layer of polymer on the surface of sandwich polystyrene magnetic beads by cross-linking 1,4-butanediol diglycidyl ether (BDE) and erythritol (Ery) in a certain ratio, thereby forming a stable epoxy group. This innovative method significantly enhances the thermal stability of the magnetic beads, enabling them to extend long-term storage stability. By comparing and analyzing key indicators such as particle size changes, sedimentation rates, and cyclic magnetic fraction recovery rates of magnetic beads under different conditions, we verified the stability of magnetic beads in high temperature environments, thereby proving the effectiveness of this method.

[0031] 2. The method provided by the present invention optimizes the epoxy modification process of the magnetic bead surface and adopts a direct cross-linking modification process, which not only simplifies the operation steps, but also ensures that the obtained epoxy magnetic beads exhibit excellent biocompatibility. In addition, this method eliminates the tedious process of functional group activation and allows direct coupling with antibodies, thereby greatly improving the efficiency and convenience of the experiment.

[0032] 3. The core protection content of this patent is to innovatively provide a method for preparing sandwich-type immunomagnetic beads with high thermal stability and high biocompatibility, as well as the wide application of these magnetic beads in multiple fields such as biomedicine and analytical chemistry. In addition, this epoxy cross-linking layer modification technology is also applicable to other materials with surface amino groups, further expanding its application potential in different fields.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] 1. By evenly cross-linking a layer of epoxy polymer on the surface of polystyrene magnetic beads, we not only retain the high magnetic properties of the beads, but also significantly improve their overall thermal stability. This improvement makes the beads have long-term storage stability and is suitable for a wider range of application scenarios.

[0035] 2. Compared with the existing epoxy modification technology, the use of 1,4-butanediol glycidyl ether combined with erythritol for cross-linking can ensure the uniformity and efficiency of the cross-linking process, thereby significantly improving the overall performance of the magnetic beads. This cross-linking method enables the magnetic beads to exhibit excellent stability, and the resulting cross-linked layer has a denser network structure and smaller pore size, which not only enhances the mechanical strength of the magnetic beads, but also improves their adsorption efficiency.

[0036] 3. In the experiment of the present invention, we adopted an innovative method, namely, introducing epoxy groups into the outer layer of magnetic beads, which enables the magnetic beads to directly react with the amino groups of antibodies and fix them without the need for additional functional group activation steps, thereby simplifying the entire coupling process. Compared with silicon-coated magnetic beads that require activation of carboxyl groups, this method is not only easy to operate, but also more efficient. In addition, the introduction of erythritol brings antioxidant properties to the magnetic beads, which helps to reduce lipid peroxidation and alleviate the body's oxidative stress response. These properties are crucial to improving the long-term stability and biocompatibility of magnetic beads. At the same time, the low toxicity and excellent biocompatibility of erythritol also provide guarantees for the application safety of magnetic beads. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 It is a schematic diagram of the synthesis route structure of the sandwich-type immunomagnetic beads in Example 1 of the present invention and the characterization results of the intermediate product PMPMS and the target product PMPMS@HBP;

[0038] Figure 2a It is the characterization result of the hydrated particle size of the products of each step of Example 1;

[0039] Figure 2b It is the Zeta potential characterization result of the products of each step of Example 1;

[0040] Figure 2c It is the infrared functional group characterization result of the nanoparticles at each stage in the preparation process of the sandwich-type immunomagnetic beads of the present invention;

[0041] Figure 3 The TEM images of the PMPMS obtained in step 3 of Example 1 and the magnetic nanoparticles finally synthesized in Examples 1-4 are compared;

[0042] Figure 4 The particle size characterization and Zeta potential characterization results of the PMPMS obtained in step 3 of Example 1 and the magnetic nanoparticles finally synthesized in Examples 1-6;

[0043] Figure 5a It is the sedimentation diagram of three magnetic bead materials, PMPMS obtained in step 3 of Example 1, PMPMS@HBP, the final product of Example 1, and PMPM@HBP, the final product of Example 7, after being mixed and left to stand for 1 hour for seven days (from left to right);

[0044] Figure 5b The particle size and PDI change results of the three magnetic bead materials, PMPMS obtained in step 3 of Example 1, PMPMS@HBP, the final product of Example 1, and PMPM@HBP, the final product of Example 7, were placed at 37°C for seven days in total;

[0045] Figure 5c The absorbance change results of the three magnetic bead materials, PMPMS obtained in step 3 of Example 1, PMPMS@HBP, the final product of Example 1, and PMPM@HBP, the final product of Example 7, were dispersed in water at a concentration of 2 mg / mL and placed at 37°C for a number of days (a total of seven days);

[0046] Figure 6a hysteresis curves of the oil phase Fe3O4 nanoparticles in Example 1, the PMPMS obtained in step 3 of Example 1, and the final product PMPMS@HBP in Example 1;

[0047] Figure 6b The magnetic properties of the final product PMPMS@HBP (Example 1) in three solutions at a dispersion concentration of 2 mg / mL;

[0048] Figure 6c It is the natural sedimentation rate diagram of the final product PMPMS@HBP (Example 1) in water at a dispersion concentration of 2 mg / mL.

[0049] Figure 7 This is the comparison result of clinical testing between the PMPMS@HBP magnetic beads synthesized in Example 1 of the present invention and the Thermo Fisher MyOneTM commercial magnetic beads. DETAILED DESCRIPTION

[0050] The mass concentration of ammonia water in the embodiment of the present invention is 25-28%.

[0051] The preparation method of the polystyrene microspheres PS-COOH in the embodiment of the present invention is as follows: weigh 0.7g of polyvinyl pyrrolidone and dissolve it in 50mL of ethanol mixed solution (the volume ratio of ethanol to water is 9:1). After the reaction device is vented with nitrogen, the temperature is gradually raised to 70°C. Add 6.5mL of styrene monomer, 0.09g of initiator-azobisisobutyronitrile and 0.2mL of functional monomer-acrylic acid; the stirring speed is 300rpm. After the reaction is allowed to react for 4h, use a syringe pump device to add 2.4mL of anhydrous ethanol solution containing 3.05mL of divinylbenzene dropwise within 2h. After the dropwise addition is completed, continue to stir the reaction solution and continue the reaction for 20h. After the synthesis is completed, wash the PS-COOH with an ethanol solution, and finally place the synthesized PS-COOH in a vacuum drying oven and dry it at 40°C for 24h to obtain polystyrene microspheres PS-COOH (with a diameter of about 1.5μm).

[0052] Example 1: A method for preparing sandwich-type immunomagnetic beads with high thermal stability

[0053] 1. Synthesis of oil-phase Fe3O4 nanoparticles

[0054] Weigh 0.708g of ferric acetylacetonate and 2.02g of dodecanediol into a three-necked flask, then add 10mL of dibenzyl ether, 4mL of oleic acid and 4mL of oleylamine, and ultrasonically treat to dissolve the solid in the mixed solution. Set up an anhydrous and oxygen-free device and operate: evacuate the reaction device for 30s and then pass nitrogen for 30s. After three cycles, switch to the evacuation state, and slowly raise the system temperature to 50°C. After the low-cost impurities are completely evacuated, switch to the nitrogen state and keep the nitrogen blowing out evenly. Heat to 200°C and stir vigorously for 30min, then continue to heat to 285°C, stir vigorously for 2h, and end the reaction. After the reaction is completed, the solution is cooled to room temperature, methanol solution is added to the crude solution to precipitate the particles, magnetic separation, chloroform solution is added to the precipitate to dissolve the magnetic particles, and methanol is repeatedly used for washing to obtain oil-phase Fe3O4 nanoparticles, which are finally dispersed in toluene (the dispersion concentration of oil-phase Fe3O4 nanoparticles in toluene is 16mg / mL).

[0055] 2. Ultrasonic assembly of two layers of oil-phase ferroferric oxide in polystyrene by swelling method

[0056] At room temperature, 20 mg of polystyrene microspheres PS-COOH (diameter of about 1.5 μm) were dispersed in 2 mL of toluene solution overnight (about 12 h). With the help of ultrasonic treatment, 1 mL of the toluene solution of oil phase Fe3O4 nanoparticles obtained in step 1 (containing 16 mg of Fe3O4) was impregnated into the swollen functionalized polystyrene microspheres and ultrasonicated at room temperature for 15 min. Magnetic separation, washing with ethanol, shrinking the microspheres, and obtaining an assembly of the first layer of Fe3O4 magnetic nanoparticles, recorded as PS-MNPs. The PS-MNPs obtained above were dispersed in 40 mL of ethanol solution containing 14 mg of polyethyleneimine (PEI), rotated and incubated at 300 rpm at room temperature for 2 h, washed three times with ethanol after magnetic separation, and then 16 mg of oil-phase Fe3O4 nanoparticles were added to 6 mL of a mixed solution of n-hexanol and toluene (volume ratio 3:1) to assemble a second layer of Fe3O4 magnetic nanoparticles. Ultrasonic treatment was performed at room temperature for 15 min to obtain a mixed solution containing microsphere assemblies assembled with two layers of oil-phase ferrosoferric oxide, which was recorded as a PMPM mixed solution.

[0057] 3. Sandwich type polystyrene magnetic beads with silicon coating on the surface

[0058] The mixed solution of PMPM obtained in step 2 was magnetically separated, the supernatant was removed, 400 μL of n-octyltrimethoxysilane (OTMS) was added, and ultrasonic mixing was uniform. Then, a mixed solution of 30 mL of methanol and 750 μL of ammonia water was quickly added and ultrasonically mixed for 30 min. After the reaction was completed, the clear solution was removed by magnetic separation, and the impurities on the surface of the magnetic beads were washed with methanol, and then centrifuged and dried. 66 mL of ultrapure water was added to the precipitate, stirred at room temperature for 24 h, and dispersed in ultrapure water by centrifugation to obtain magnetic beads modified with surface organosilane. Finally, the magnetic beads modified with organosilane were magnetically separated and dispersed in a mixed solution of 15 mL of ethanol and 5 mL of ultrapure water. 0.625 mL of ammonia water and 15.4 μL of tetraethyl silicate (TEOS) were added to the above solution. After reacting for 3 h, 15.4 μL of TEOS was added to grow a silica shell on the surface of the magnetic beads. After the reaction was completed, the product was magnetically separated and washed with ethanol to obtain silicon-coated polystyrene magnetic beads, which were recorded as PMPMS.

[0059] 4. Surface amination of sandwich polystyrene magnetic beads

[0060] Disperse the PMPMS obtained in step 3 in 10 mL of ethanol, add 5 μL of 3-aminopropyltriethoxysilane (APTMS) and 75 μL of ammonia water, react on a shaker at 200 rpm for 2 h, then add 5 μL of APTMS (APTMS is added stepwise to fully aminize the magnetic beads), continue to react for 2 h, then add 5 μL of APTMS again, react for another 2 h, and then magnetically separate, wash twice with ethanol and three times with ultrapure water to obtain aminated magnetic beads, recorded as PMPMS-NH2, and stored in ultrapure water.

[0061] 5. Cross-linking of the surface of sandwich polystyrene magnetic beads to form a polymer layer (PMPMS@HBP)

[0062] ①Magnetically separate the aqueous solution of PMPMS-NH2 obtained in step 4 and disperse it in 40 mL of borate buffer (BBS 9.0) at pH = 9.0 to obtain a magnetic bead solution. ②Dissolve 160 mg of 1,4-butanediol diglycidyl ether (BDE) in BBS 9.0 solution to prepare a BDE solution with a concentration of 20 mg / mL. ③Dissolve 65.87 mg of erythritol (Ery) in BBS 9.0 solution to prepare an Ery solution with a concentration of 20 mg / mL.

[0063] First, add the prepared BDE solution to the reaction glass bottle, slowly add the magnetic bead solution, then add the Ery solution, and react at room temperature on a shaker at 200 rpm for 24 hours. After the reaction, separate by magnetic separation and wash with ultrapure water to obtain PMPMS@HBP (1:8).

[0064] The schematic diagram of the synthesis route of the sandwich-type immunomagnetic beads in Example 1 of the present invention and the characterization results of the intermediate product PMPMS and the target product PMPMS@HBP are summarized in Figure 1 middle, Figure 1 (a) is a schematic diagram of the synthesis route structure of sandwich-type immunomagnetic beads. Figure 1 (b1, b2) are single particle and local TEM images of PS-COOH nanoparticles and large-scale and single particle SEM images. Figure 1 (c1, c2) are single particle and local TEM images of the intermediate product PMPMS nanoparticles obtained in step 3 of Example 1, as well as large-scale and single particle SEM images. Figure 1 (d1, d2) are single particle and local TEM images of the target product PMPMS@HBP nanoparticles obtained in step 5 of Example 1, as well as large-scale and single particle SEM images.

[0065] from Figure 1 It can be seen that the oil-phase ferroferric oxide nanoparticles are loaded on the surface of the PS-COOH nanoparticles and wrapped with a layer of silicon layer (to prevent the leakage of the oil-phase ferroferric oxide nanoparticles). Figure 1 (d1, d2) The electron microscopy images show that a thin polymer layer is added to the surface.

[0066] Embodiment 2:

[0067] A method for preparing sandwich immunomagnetic beads with high thermal stability, wherein the preparation steps are repeated in Example 1, the only difference being that "in step 5, the mass of BDE is replaced by 20 mg, and the mass of Ery is replaced by 8.23 ​​mg", and the other conditions remain unchanged, and PMPMS@HBP (1:1) is finally obtained.

[0068] Embodiment 3:

[0069] A method for preparing sandwich immunomagnetic beads with high thermal stability, wherein the preparation steps are repeated in Example 1, the only difference being that "in step 5, the mass of BDE is replaced by 80 mg, and the mass of Ery is replaced by 32.935 mg", and the other conditions remain unchanged, and PMPMS@HBP (1:4) is finally obtained.

[0070] Embodiment 4:

[0071] A method for preparing sandwich immunomagnetic beads with high thermal stability, wherein the preparation steps are repeated in Example 1, the only difference being that "in step 5, the mass of BDE is replaced by 320 mg, and the mass of Ery is replaced by 131.74 mg", and the other conditions remain unchanged, and PMPMS@HBP (1:16) is finally obtained.

[0072] Embodiment 5:

[0073] A method for preparing sandwich immunomagnetic beads with high thermal stability, wherein the preparation steps are repeated in Example 1, the only difference being that "the reaction time in step 5 is replaced with 36 h", and the other conditions remain unchanged, and finally PMPMS@HBP (cross-linking time 36 h) is obtained.

[0074] Embodiment 6:

[0075] A method for preparing sandwich immunomagnetic beads with high thermal stability, wherein the preparation steps are repeated in Example 1, the only difference being that "the reaction time in step 5 is replaced with 48 h", and the other conditions remain unchanged, and finally PMPMS@HBP (cross-linking time 48 h) is obtained.

[0076] Embodiment 7:

[0077] A method for preparing sandwich immunomagnetic beads with high thermal stability, wherein the preparation steps are repeated in Example 1, except that: in step 3, the step of growing a thin layer of silicon dioxide by hydrolysis of tetraethyl orthosilicate TEOS is omitted, that is, the specific operation of step 3 of Example 7 is as follows: the mixed solution of PMPM obtained in step 2 is subjected to magnetic separation, the clear solution is removed, 400 μL of n-octyltrimethoxysilane (OTMS) is added, and ultrasonic mixing is uniform. Then, a mixed solution of 30 mL of methanol and 750 μL of ammonia water is quickly added and ultrasonically mixed for 30 min. After the reaction is completed, the clear solution is removed by magnetic separation, and impurities on the surface of the magnetic beads are washed with methanol, and then centrifuged and dried. 66 mL of ultrapure water is added to the precipitate, stirred at room temperature for 24 h, and centrifuged and dispersed in ultrapure water to obtain magnetic beads modified with surface organosilane. The remaining conditions of Example 7 remain unchanged, and PMPM@HBP is finally obtained.

[0078] The hydrated particle size characterization results, Zeta potential characterization results and infrared functional group characterization results of the nanoparticles in each stage of Example 1 are respectively shown in Figure 2a , Figure 2b and Figure 2c , Figure 2b The potential change is used to prove whether the magnetic beads are synthesized at each step, thereby proving that the surface polymer grafting is successful; Figure 2c This is an infrared functional group characterization diagram, which also proves that the surface epoxy polymer coating is successful.

[0079] Figure 2a When testing the hydrated particle size, the material is dispersed in water at a concentration of 0.05 mg / mL for testing.

[0080] Figure 2a-2cThe PS-COOH in the above corresponds to the PS-COOH spheres in Example 1; PS-MNPs corresponds to the assembly loaded with a layer of oil-phase ferrosoferric oxide in step 2 of Example 1; PMPM corresponds to the nanoparticle assembly loaded with a second layer of oil-phase ferrosoferric oxide after adding PEI in step 2 of Example 1; PMPM@HBP corresponds to the final synthesized magnetic nanoparticles in Example 7; PMPMS is the silicon-coated magnetic nanoparticles in step 3 of Example 1; PMPMS-NH2 is the sandwich polystyrene magnetic beads after amino treatment in step 4 of Example 1; PMPMS@HBP is the final synthesized magnetic nanoparticles in Example 1.

[0081] The TEM images of the PMPMS obtained in step 3 of Example 1 and the magnetic nanoparticles finally synthesized in Examples 1-4 are compared in FIG. Figure 3 , Figure 3 (ae) is the TEM morphology of a single magnetic bead. Figure 3 (fj) are Figure 3 (ae) Local TEM images of the particle surface corresponding to a single particle. Figure 3 It can be seen that as the cross-linking ratio of magnetic beads to polymer increases, the thickness of the outer polymer layer of the magnetic beads increases accordingly.

[0082] The particle size characterization and Zeta potential characterization results of the PMPMS obtained in step 3 of Example 1 and the magnetic nanoparticles finally synthesized in Examples 1-6 are summarized in Figure 4 middle, Figure 4 (a) PMPMS before cross-linking, particle size changes of four magnetic beads with different cross-linking ratios (1:4, 1:8, 1:16); Figure 4 (b) PMPMS before cross-linking, potential changes of four magnetic beads with different cross-linking ratios (1:4, 1:8, 1:16); Figure 4 (c) PMPMS before cross-linking, particle size changes of four types of magnetic beads at different cross-linking times (24 h, 36 h, and 48 h); Figure 4 (d) PMPMS before cross-linking, potential changes of four magnetic beads at different cross-linking times (24h, 36h, 48h). Figure 4 (a)- Figure 4 (b) is a comparison of the characterization results of the PMPMS obtained in step 3 of Example 1 and the magnetic nanoparticles finally synthesized in Examples 1-4, Figure 4 (c)- Figure 4 (d) is a comparison of the characterization results of the PMPMS obtained in step 3 of Example 1 and the magnetic nanoparticles finally synthesized in Examples 1, 5-6. Figure 4The potential change shows that the potential of the magnetic bead surface is positive after amino treatment. As the cross-linking layer is grafted, the potential changes accordingly. It can be seen that the potentials are similar when the cross-linking ratio is 1:8 and 1:16, indicating that the epoxy groups on the surface are basically saturated. Figure 4 It can be seen from the change in particle size that the magnetic beads agglomerated after 48 hours of cross-linking, resulting in a sudden increase in particle size and peak width.

[0083] The three magnetic bead materials PMPMS obtained in step 3 of Example 1, PMPMS@HBP, the final product of Example 1, and PMPM@HBP, the final product of Example 7, were subjected to a thermal stability test experiment: the magnetic bead materials were dispersed in water at a concentration of 2 mg / mL. When characterizing the performance, the dispersion was ultrasonically dispersed and then placed for 1 hour. This method was used for testing for 7 days. Every day, the dispersion was ultrasonically dispersed and then placed for 1 hour before the performance test was performed. The three magnetic bead materials (PMPMS, PMPMS@HBP, PMPM@HBP) were placed for seven days (a total of seven days, from left to right) and then mixed and allowed to stand for 1 hour. See the sedimentation diagram for the three magnetic bead materials (PMPMS, PMPMS@HBP, PMPM@HBP) Figure 5a , the particle size and PDI changes of the samples placed at 37°C for seven days (total 7 days) refer to Figure 5b , the absorbance change after being placed at 37℃ for seven days (a total of seven days) Figure 5c .from Figure 5a-5c It can be seen that the dispersion of the magnetic beads decreases as they are placed at 37°C for one week. Compared with PMPMS coated with only silicon and PMPM@HBP coated with only polymer, the dispersion of the magnetic beads decreases after being placed at 37°C for one week. (It is commercially recognized that the beads can be placed at 37°C for one week, but can actually be stored at 4°C for one year.)

[0084] The hysteresis curves of the oil phase Fe3O4 nanoparticles in Example 1, the PMPMS obtained in step 3 of Example 1, and the final product PMPMS@HBP in Example 1 are shown in FIG. Figure 6a , characterizing the magnetic change. Figure 6b The magnetic separation performance of the final product PMPMS@HBP (Example 1) in three solutions at a dispersion concentration of 2 mg / mL shows that PMPMS@HBP magnetic beads can adapt to different biological detection buffers without aggregation. Figure 6b The three solutions are: 1) PBS: 10mM PBS (pH=7.4) buffer solution. Taking 1L of buffer solution as an example, 1.44g disodium hydrogen phosphate, 0.24g potassium dihydrogen phosphate, 8g sodium chloride are required, and the solvent is water. 2) FBS is fetal bovine serum. 3) water is ultrapure water.

[0085] Figure 6bThe magnetic capture efficiency is the efficiency of the magnet in capturing magnetic beads within 1 minute. The magnetic capture efficiency is calculated by testing the absorbance value of the magnetic beads in the suspension stock solution, magnetically separating the magnetic beads in the suspension stock solution using a magnetic stand, and taking the supernatant to test the absorbance value. Magnetic capture efficiency = (absorbance value of the suspension stock solution - absorbance value of the supernatant) / absorbance value of the suspension stock solution * 100%.

[0086] Figure 6c The figure shows the natural sedimentation rate of the final product PMPMS@HBP (Example 1) in water at a dispersion concentration of 2 mg / mL. Figure 6c The absorbance in is the absorbance of the supernatant after natural sedimentation in water. It can be seen that PMPMS@HBP takes about 6 hours to settle completely and has good dispersibility in the solution.

[0087] The PMPMS@HBP magnetic beads synthesized in Example 1 were compared with the Thermo Fisher MyOneTM commercial magnetic beads for clinical testing. This application study was conducted in cooperation with Mekang Biotechnology Co., Ltd., using Mekang Biotechnology MS-i3080 fully automatic chemiluminescence immunoassay for chemiluminescence detection, and the clinical sample tested was testosterone. The horizontal axis is the chemiluminescence signal obtained by the detection of the PMPMS@HBP magnetic beads synthesized in Example 1 of this application, and the vertical axis is the relevant detection signal of the Thermo Fisher My OneTM magnetic beads. The test results are shown in Figure 7 , the correlation of the fitted linear equation is good (R 2 =0.996), the detection performance of PMPMS@HBP is close to that of commercial magnetic beads, proving that PMPMS-COOH has excellent clinical detection performance.

[0088] get Figure 7 The experimental steps for testing the results are as follows:

[0089] 1) First, a series of testosterone solutions with different concentration gradients were prepared using PBS buffer (0.01M, pH=7.4) as solvent, with the testosterone concentration range of 0-25ng / mL. 100μL of testosterone solutions of different concentrations were added to 100μL of PBS buffer containing 0.5mg / mL PMPMS@HBP magnetic beads, which are testosterone immune capture probes, and 100μL of 0.125mg / mL acridinium ester-mouse anti-testosterone monoclonal antibody 2 (mAb2) solution was added. The mixture was shaken and incubated in a shaker at 37°C for 18 minutes. After the incubation, the beads were magnetically separated and washed three times with washing buffer. After magnetic separation and washing, the beads were redispersed in 500μL PBS buffer (0.01M, pH=7.4) to obtain the immune complex test solution. When the chemiluminescence detection was performed subsequently, 50 μL of 5 mM hydrogen peroxide and 100 μL of 1 mM sodium hydroxide solution were added to the immune complex test solution, and the chemiluminescence intensity value of the immune complex was measured using an automatic chemiluminescence immunoassay instrument (Meikang Biotechnology MS-i3080).

[0090] 2) Using the concentration of testosterone as the horizontal axis, the PMPMS@HBP magnetic beads (testosterone immune capture probe, 100μI PBS buffer containing 0.5mg / mL PMPMS@HBP magnetic beads) of Example 1 of the present invention were tested for testosterone by chemiluminescence competition method, and the luminescence intensity was used as the horizontal axis, and the detection buffer was PBS buffer (0.01M, pH=7.4). In addition, the chemiluminescence intensity value of the immune complex of commercial magnetic beads (purchased from ThermoFisher) and testosterone was tested according to the above steps. The difference in the detection steps was only that "100HL PBS buffer containing 0.5mg / mIPMPMS@HBP magnetic beads was replaced with 100HL PBS buffer containing 0.5mg / mL commercial magnetic beads", and the other steps remained unchanged, thereby measuring the chemiluminescence value of the immune complex of the commercial magnetic beads as the vertical axis, and then fitting the linear equation.

Claims

1. A method for preparing sandwich-type immunomagnetic beads with high thermal stability, characterized in that Using polystyrene microspheres as templates, oil-phase Fe3O4 nanoparticles were introduced into polystyrene microspheres by a swelling method. Then, octyltrimethoxysilane (OTMS) was used to undergo a hydrolysis-condensation reaction on the surface of the microsphere assembly to achieve a phase transfer of the microsphere assembly from the organic phase to the aqueous phase. Then, tetraethyl orthosilicate (TEOS) was hydrolyzed to grow a thin layer of silica by the Stöber method to achieve the coating of the outermost organic shell layer to prevent leakage of magnetic particles. The obtained silicon-coated polystyrene magnetic beads were then surface-amino-modified and then cross-linked on their surface with 1,4-butanediol diglycidyl ether (BDE) and erythritol (Ery) to form an epoxy polymer layer, thereby obtaining a sandwich-type immunomagnetic bead with a cross-linked epoxy polymer layer introduced into the outer layer.

2. The method for preparing a sandwich-type immunomagnetic bead with high thermal stability as claimed in claim 1, characterized in that The oil phase Fe3O4 nanoparticles are assembled on polystyrene microspheres in two layers, and the assembly steps are as follows: S1 one-layer assembly: After the microsphere template is swollen in toluene good solvent at room temperature overnight, the first part of oil phase Fe3O4 nanoparticles is added and ultrasonicated at room temperature for 10-30min, magnetically separated, and then the microsphere assembly is shrunk with ethanol poor solvent; S2 two-layer assembly: add the ethanol dispersion of polyethyleneimine PEI to the assembly of step S1, the mass ratio of the microsphere template to PEI in the assembly is 1:0.5-2, rotate and incubate at room temperature at a speed of 100-400rpm for 1-3h, and wash with ethanol after magnetic separation to obtain the middle layer assembly filled with PEI, then add the second part of oil phase Fe3O4 nanoparticles and n-hexanol-toluene mixed solution, ultrasonicate at room temperature for 10-30min, magnetic separation, and wash with ethanol to complete the preparation.

3. A method for preparing a sandwich-type immunomagnetic bead with high thermal stability as claimed in claim 2, characterized in that The mass ratio of the first part of oil-phase Fe3O4 nanoparticles to the second part of oil-phase Fe3O4 nanoparticles is 1:0.5-2, preferably 1:0.8-1.2, and the ratio of the total mass of the two parts of oil-phase Fe3O4 nanoparticles to the mass of the microsphere template is 1-2:1, preferably 1.5-1.6:

1.

4. A method for preparing a sandwich-type immunomagnetic bead with high thermal stability as claimed in claim 2, characterized in that In step S2, in the n-hexanol-toluene mixed solution, the volume ratio of n-hexanol to toluene is 2-4:1, preferably 3:1; the dispersion concentration of the second part of oil phase Fe3O4 nanoparticles in the n-hexanol-toluene mixed solution is 1-5 mg / mL.

5. The method for preparing a sandwich-type immunomagnetic bead with high thermal stability as claimed in claim 1, characterized in that The preparation method of the oil-phase Fe3O4 nanoparticles is as follows: adding iron salt, dodecanediol, dibenzyl ether, oleic acid and oleylamine into a reaction bottle, dissolving the solid by ultrasound, injecting nitrogen to completely replace the air in the reaction bottle, heating the temperature to 180-200°C and vigorously stirring for 20-40 minutes, then continuing to heat the temperature to 285-300°C, vigorously stirring for 1-3 hours, and then ending the reaction; after cooling to room temperature, adding methanol to the crude solution to precipitate the magnetic particles generated by the reaction, magnetic separation, absorbing the supernatant, adding chloroform to the precipitate to dissolve the magnetic particles, adding methanol again to precipitate the particles, and finally dissolving the precipitate and storing it in toluene for later use.

6. A method for preparing a sandwich-type immunomagnetic bead with high thermal stability as claimed in claim 5, characterized in that In the preparation method of the oil-phase Fe3O4 nanoparticles, the iron salt is ferric acetylacetonate, and the feed ratio of the iron salt, dodecanediol, dibenzyl ether, oleic acid and oleylamine is (0.6-0.8) g: (1.8-2.4) g: (8-12) mL: (3-5) mL: (3-5) mL.

7. The method for preparing a sandwich-type immunomagnetic bead with high thermal stability as claimed in claim 1, characterized in that The silicon-coated polystyrene magnetic beads are amino-modified in three steps, and the process is as follows: 1) Disperse the silicon-coated polystyrene magnetic beads in ethanol, add the first part of 3-aminopropyltriethoxysilane APTMS and ammonia water, and react at 100-300 rpm in a shaker for 1-3 hours; 2) Then add the second part of 3-aminopropyltriethoxysilane APTMS and continue to react for 1-3 hours, then add the third part of 3-aminopropyltriethoxysilane APTMS and continue to react for 1-3 hours, separate by magnetic separation, and wash with ethanol and water in turn, and the amino modification is completed; The volume ratio of the first part, the second part and the third part of APTMS is 1:0.8-1.2:0.8-1.2, the total volume of the three parts of APTMS and the mass ratio of the microsphere template in the silicon-coated polystyrene magnetic beads is 0.5-1:1, the volume unit is μL, and the mass unit is mg; Step 1) The mass concentration of the ammonia water is 25-28%, and the volume of the ammonia water is 0.5-1% of the volume of the ethanol; Step 1) Silica-coated polystyrene magnetic beads are dispersed in ethanol at a concentration of 1-10 mg / mL.

8. The method for preparing a sandwich-type immunomagnetic bead with high thermal stability as claimed in claim 1, characterized in that The preparation method of the epoxy polymer layer is as follows: the aminated magnetic beads, 1,4-butanediol diglycidyl ether BDE and erythritol Ery are dispersed in a borate buffer solution with a pH of 9.0, reacted at a rotation speed of 100-300 rpm in a shaker at room temperature for 20-30 hours, and after the reaction is completed, magnetic separation is performed and washed with ultrapure water to complete the preparation.

9. The method for preparing a sandwich-type immunomagnetic bead with high thermal stability as claimed in claim 8, characterized in that The mass ratio of BDE to Ery is 2-3:

1.

10. The method for preparing a sandwich immunomagnetic bead with high thermal stability as claimed in claim 8, characterized in that The mass ratio of the BDE to the microsphere template in the aminated magnetic beads is 1-16:1, preferably 4-8:1.

Citation Information

Patent Citations

  • Method for preparing stable monodisperse crosslinked polystyrene magnetic microspheres

    CN114591726A

  • Swelling and layer-by-layer assembly-based sandwich type crosslinked polystyrene analysis magnetic bead as well as preparation method and application of swelling and layer-by-layer assembly-based sandwich type crosslinked polystyrene analysis magnetic bead

    CN116626289A

  • Immunomagnetic bead for chemiluminescence immunodetection as well as preparation method and application of immunomagnetic bead

    CN119001086A

Cited By

  • Magnetic-metal supported nano-enzyme with high HRP (horse radish peroxidase) catalytic efficiency and application of magnetic-metal supported nano-enzyme

    CN121648938A

  • Novel chemiluminescence immunomagnetic bead as well as preparation process and application thereof

    CN122042960A

  • Degradable epoxy resin containing boric acid ester structure and preparation method thereof

    CN122502615A